(untitled) (Proceedings of the International Conference on Public Health, 2023)
Dental caries and periodontal disease are common among the school children in rural areas. It is highly prevalent and become a “silent epidemic”. According to national oral health survey 2002-2003, 39.17% of 12 years have caries and in rural area it is 40.68%. In the fight against dental caries Ministry of health has introduced “Save the Molar” project where fissure sealant is applied in schoolchildren by school dental therapists. As fissure sealant was a new introduction to the government system, the study aims to assess the retention of fissure sealant applied by SDT. Six SDT were selected from a rural district in Sri Lanka and they were trained for 2 days on selection of children and application of glass ionomer fissure sealant. Three of them had applied glass iomoner based fissure sealant in a mobile setup while the other three had applied the same fissure sealant in the school dental clinics. After a period of six months, the fissure sealants were reviewed to see whether they are fully intact, broken or completely dislodged. All the children were between ages 9-11.76.84% of the fissure sealant was present in the molar teeth after six months and 11.33% were broken and 11.82% were and completely dislodged from the teeth. In clinic setup 75.61% fully intact fissure sealant while 12.68% and11.70% were broken or completely dislodged respectively. However, in mobile setup results were much better, 79% of the fissure sealants were intact while 8.95% and 11.94% are either broken or dislodged respectively.This study shows no much difference in retention of glass ionomer fissure sealant applied in clinic setup and mobile setup. Overall retention percentages are high.